IDENTIFICATION OF RISK FACTORS FOR CEREBRAL ANEURYSM RUPTURE THROUGH STATISTICAL ANALYSIS - Çelikdemir, Meltem Yavuz; Akbal, Ayhan (My University, 2025)
This study examines the relationship between clinical, morphological, and hemodynamic factors and the risk of rupture in individuals with cerebral aneurysms. A logistic regression model was developed to identify variables influencing aneurysm rupture. The results indicate that age (p=0.0074) and comorbidities (p=0.0157) have a statistically significant effect on rupture probability. Variance Inflation Factor (VIF) analysis revealed multicollinearity between the length and width variables (VIF=3.96), while no such relationship was detected for other variables. Chi-square and Mann-Whitney U tests confirmed that age, aneurysm type, and comorbidities differ significantly between patients with and without rupture (p<0.05). Post-hoc analysis further supported statistically significant differences between groups concerning age (p=0.0001), aneurysm type (p=0.0004), and comorbidities (p=0.0039). Fisher’s exact test demonstrated a significant association between rupture risk and variables such as diabetes, ischemic cerebrovascular disease, a history of ischemic stroke, and coronary artery predisposition (p<0.05). This comprehensive analysis highlights the critical role of age, aneurysm type, and specific comorbidities in determining the risk of cerebral aneurysm rupture.
Keywords: Statistical analysis; cerebral aneurysm; rupture risk